2021
DOI: 10.1113/jp280917
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‐related microRNAs as modulators of the cardiovascular system: the role of epicardial adipose tissue

Abstract: information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 93 publications
(215 reference statements)
0
10
0
Order By: Relevance
“…Vitro studies in rat cardiomyocytes have found that increased expression of miR-208a secreted by EAT could damage mitochondrial β-oxidation, thereby changing the contractile function of the myocardium [ 37 ] through the renin-angiotensin-aldosterone system. Tran et al discovered that the increase of miR-155 and miR-302a-3p in the plasma of patients with atrial fibrillation was positively correlated with the thickness of EAT, which may be related to heart remodeling [ 38 , 39 ]. An increase in the volume of TNF-α secreted by EAT could induce changes in cardiomyocyte apoptosis, cardiac dilatation, and extracellular matrix remodeling [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitro studies in rat cardiomyocytes have found that increased expression of miR-208a secreted by EAT could damage mitochondrial β-oxidation, thereby changing the contractile function of the myocardium [ 37 ] through the renin-angiotensin-aldosterone system. Tran et al discovered that the increase of miR-155 and miR-302a-3p in the plasma of patients with atrial fibrillation was positively correlated with the thickness of EAT, which may be related to heart remodeling [ 38 , 39 ]. An increase in the volume of TNF-α secreted by EAT could induce changes in cardiomyocyte apoptosis, cardiac dilatation, and extracellular matrix remodeling [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Again, using novel molecular imaging probes as described above in Sections "Imaging Inflammation" and "Cardiovascular MR in HFpEF", it is now possible not only to assess key leukocyte populations within the myocardium, but also to measure myocardial fibrosis via cardiac extracellular volume. Additionally, the modulation of adipokine function (including a reduction in serum leptin) has been linked with altered epicardial fat deposition profiles [190,191], the changes of which can be straightforwardly assessed using imaging.…”
Section: A Future Role For Advanced Imaging In Hfpef?mentioning
confidence: 99%
“…UCP-1 uncouples mitochondrial respiration from ATP production, thus facilitating non-shivering thermogenesis, which is involved in thermoregulation. In the absence of aponeurotic or connective tissues between the EAT and the myocardium, EAT provides a rich local source of free fatty acids that support the high energy demands of nearby cardiomyocytes, thus providing cardiac energy storage [8]. EAT also secretes multiple cytokines (such as adiponectin) that limit myocardial inflammation and fibrosis.…”
Section: Eat Histology and Physiologymentioning
confidence: 99%